Ethical issues in genetic medicine. Issue 8 (August 2017) - Lucassen, Anneke; Farsides, Bobbie
'It runs in my family' is an expression commonly used by patients. Family history is recorded as part of new patient checks, and it is usual to ask patients with symptoms suggestive of a disease with an inherited component about family history of that disease. As genetic technology has become cheaper and faster, it is increasingly applied outside the specialty of clinical genetics: paediatricians use comparative microarrays, prenatal testing is offered to many women in pregnancy and, in the fields of oncology and cardiology, genetic predispositions to disease are frequently sought. GPs are already seeing these developments impact on their practice and will inevitably become more involved in the genetic management of families as testing becomes more widespread.